Gynaecological cancers coexisting with pregnancy – a literature review - Anna Skrzypczyk-Ostaszewicz; Maryna Rubach (Contemporary Oncology, 2016)
The coexistence of malignant tumour and pregnancy is a state of simultaneous occurrence of two completely contradictory philosophical and biological phenomena – the development of a new life and a life-threatening terminal illness. Finally, a physician – in fact the whole team of doctors – is facing the fight for two lives: of the mother and her unborn child. The incidence of malignant disease in pregnancy is 0.05 to 0.1%. This condition is a major challenge for physicians because there are no randomised studies that could be the basis to choose the therapeutic methods – the medical knowledge merely comes from case reports, registries, and observational studies. The following cancers most often coexist with pregnancy: gynaecological neoplasm (especially cervical and ovarian cancer), breast cancer, lymphatic system neoplasm, and melanoma. Formerly, the diagnosis was clearly the necessity of abortion. Today – although unskilled doctors still propose the only therapeutic option – termination of pregnancy is not the only solution. The past few years have seen the updating of reports and guidelines for the management of pregnant women with cancer. This paper is a review and summary of the information from these publications.